Toxicities Associated with Cisplatin-Based Chemotherapy and Radiotherapy in Long-Term Testicular Cancer Survivors - Chunkit Fung; Paul Dinh; Shirin Ardeshir-Rouhani-Fard; Kerry Schaffer; Sophie D. Fossa; Lois B. Travis (Advances in Urology)
Testicular cancer has become the paradigm of adult-onset cancer survivorship, due to the young age at diagnosis and 10-year relative survival of 95%. This clinical review presents the current status of various treatment-related complications experienced by long-term testicular cancer survivors (TCS) free of disease for 5 or more years after primary treatment. Cardiovascular disease and second malignant neoplasms represent the most common potentially life-threatening late effects. Other long-term adverse outcomes include neuro- and ototoxicity, pulmonary complications, nephrotoxicity, hypogonadism, infertility, and avascular necrosis. Future research efforts should focus on delineation of the genetic underpinning of these long-term toxicities to understand their biologic basis and etiopathogenetic pathways, with the goal of developing targeted prevention and intervention strategies to optimize risk-based care and minimize chronic morbidities. In the interim, health care providers should advise TCS to adhere to national guidelines for the management of cardiovascular disease risk factors, as well as to adopt behaviors consistent with a healthy lifestyle, including smoking cessation, a balanced diet, and a moderate to vigorous intensity exercise program. TCS should also follow national guidelines for cancer screening as currently applied to the general population.